Indeks Kualitas Tanah Lahan Pasang Surut pada Tiga Tipe Penggunaan Lahan di Desa Punggur Kecil Kabupaten Kubu Raya - Vera, Konselia D.; Umran, Ismahan; Hayati, Rita (Perkebunan dan Lahan Tropika, 2024)
The study was conducted in the Punggur Kecil Village, Kubu Raya Regency, on three types of land use those are langsat plantations, mixed cropping and rice fields.   Land use change or land conversion is one of the factor that decteasing soil quality. Land use changed that occurs in punggur kecil, reguires any research aim to determining the soil quality index on three types of land use, those are Langsat plantations, mixed crops and rice fields in the punggur kecil village sungai kakap, Kubu Raya District.   Soil sampling using a diagonal system at 3 study sites with 5 points. The amount of samples in the three types of land use are 15 samples. Research parameters include supporting parameters such as soil profile, structure, vegetation type, depth of ground water level, pyrite content and distance of observation location from river / sea. Soil physical properties include bulk density, moisture content in field capacity, total porosity and texture. Soil chemical properties include soil reaction (pH), N-Total, P-Available, K-exchangeble, Ca-exchangeble, Mg-exchangeble, Na- exchangeble, Base Saturation, Cation Exchange Capacity (CEC) and C-Organic. Biological properties include: earthworm population. Stages of research include determining the location of research sampling, sample analysis in the laboratory, determination of the minimum data set (MDS) with principal component analysis (PCA) as a weight index, scoring of soil indicators and determination of soil quality index. Data processing using microsof excel 2010 and statistical applications SPSS 16. The results showed langsat plantations have a soil quality index of 0.44 (medium criteria). Mixed crop land has a soil quality index value of 0.35 (low criteria). Rice fields have a soil quality index value of 0.35 (low criteria).